Development and implementation of digital solutions in healthcare: insights from the Australian tertiary hospital landscape - Schnetler, Rudolf J.; Vangaveti, Venkat N.; Crowley, Benjamin J.; Keogh, Joshua K.; Harris, Trudie; Parker, Dale; Watson, Jane; Edwards, Teresa; Westwood, Peter; Birden, Hudson; Daly, Marina; Keyes, Kieran; et al. (Frontiers in Digital Health, 2025)
BackgroundThe role of clinician-researchers in regional healthcare is challenging. Balancing patient care, academic research, and mentoring junior staff significantly burdens these dedicated professionals. Therefore, the Australian healthcare system must provide institutional support for improving clinicians' academic performance.MethodsThis paper describes two digital solutions implemented in a regional Australian Hospital and Health Service. The Audit, Quality, and Innovation Review panel simplifies the approval process using digital workflows for quality assurance and audit projects, and the Research Data Laboratory provides secure access to de-identified patient data and supports data analysis.DiscussionUnlike some countries, such as the US and UK, where financial incentives or established networks drive research integration, the Townsville Hospital and Health Service focuses on empowering clinicians to address local healthcare issues through research directly. This makes the Townsville Hospital and Health Service a standout example in Australian healthcare, highlighting the significance of specialised research infrastructure and data services for clinician-led audit projects and research. This digital health solutions approach is essential for closing the gap between research and practical application, ultimately leading to improved patient care. Importantly, as a service-embedded structure, this model may be more sustainable and effective than traditional models reliant on external funding or networks in regional settings.